How painful is a heelprick or a venipuncture in a newborn?. (17th January 2016) - Bellieni, C. V.; Stazzoni, G.; Tei, M.; Alagna, M. G.; Iacoponi, F.; Cornacchione, S.; Bertrando, S.; Buonocore, G.
Abstract: Objective : Neonates undergo many painful procedures daily, in particular venipunctures and heelpricks. Our aim was to assess how painful these procedures actually are, and how effective are the common analgesic strategies to blunt this pain. Methods : We performed a MEDLINE/PubMed research from 1999 to 2013. We retrieved all papers in English language that evaluated pain during neonatal heelprick or venipuncture and that used as score the Premature Infant Pain Profile (PIPP), a widely used scale for evaluate acute pain in term and preterm babies. Results : Fifteen papers met the inclusion criteria, using different analgesic methods. Just in one case two studies used the same analgesic method. Most analgesic procedures show a relevant level of pain. We didn't find univocal difference between heelprick and venipuncture. Topic creams, systemic analgesics, posture and oral glucose 10% have scarce analgesic effectiveness. The most effective procedures are the use of oral sweet solutions (sucrose or glucose) at concentrations greater than 20%, multisensory stimulations and non-nutritive sucking used along with 10% glucose. Conclusions : A large amount of analgesic methods was used, making comparisons difficult. Nevertheless, in the absence of analgesic treatment, heelpricks and venipunctures are moderately-severely painful, and among the proposed analgesic procedures, few seem to be effective.